2011
DOI: 10.1590/s1983-51752011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of fetal calf serum by human serum as supplementation for human fibroblast culture

Abstract: Replacement of fetal calf serum by human serum as supplementation for human fibroblast culture Replacement of fetal calf serum by human serum as supplementation for human fibroblast culture Substituição de soro bovino fetal por soro humano como suplemento para cultura de fibroblastos humanos Study conducted at the Cell Culture and Wound Healing Research Laboratory (LIM 04

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A significant amount of fibroblast cells was stained by vimentin, while the blood cells trapped in PRF during the centrifugation were not stained by vimentin, showing the possibility of PPP 10% in maintaining the viability of those human cells. The PPP provides a significant amount of platelet-derived growth factor (PDGF-AB), transforming growth factor-β1(TGF-β1) and other bioactive molecules ( 13 ) ( 9 , 10 ) and this can explain the results that showed that 10% PPP provided similar cell proliferation when compared to control group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A significant amount of fibroblast cells was stained by vimentin, while the blood cells trapped in PRF during the centrifugation were not stained by vimentin, showing the possibility of PPP 10% in maintaining the viability of those human cells. The PPP provides a significant amount of platelet-derived growth factor (PDGF-AB), transforming growth factor-β1(TGF-β1) and other bioactive molecules ( 13 ) ( 9 , 10 ) and this can explain the results that showed that 10% PPP provided similar cell proliferation when compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, xenogeneic agents could pose risks to patients’health due to their ability to generate antibodies against factor V and XI, which could cause coagulopathies ( 11 , 16 ). The PRF is rich in growth factors, platelets and fibrin,thus having high potential for clinical application ( 9 , 10 ). However, the study of PPP, which isobtained of PRF, has been poorly investigated even though ithas a high range of important biomolecules ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations